PEMBERIAN UPAH SELAMA PROSES PEMUTUSAN HUBUNGAN KERJA SEPIHAK (STUDI KASUS: PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 90/PDT.SUS-PHI/2019/PN SBY) - Shierly Florensia; Gunardi Lie (Jurnal Hukum Adigama, 2021)
Termination of Employment Relations is one of the problems that often occurs in the working relationship between workers/employees and employers. The termination of an employment relationship for the workers is a very complex problem due to the worker/labourer losing their livelihood. Termination of Employment Relations has legal consequences for both employers and workers/labor. The rights and obligations of each party must be fulfilled until there is a decision from the Industrial Relations Court, in which workers will receive legal protection, namely receiving severance pay or service pay as a substitute for termination of employment. Syamsul Fuad has worked in a position as a dynamo technician with a working period of 23 years and 6 months and will be dismissed from his job due to frequent illness by PT Jawa Trans Indah Transport without being given a fair severance pay in accordance with the law, so Syamsul Fuad filed a lawsuit with the Industrial Relations Court on The Surabaya District Court, but in the decision the workers' property rights to receive severance pay or service pay cannot be fulfilled. This research is normative with literature study data collection techniques. Like a scale that is used as a symbol of justice, the judge must also weigh in order to fulfill the workers' property rights, so that in this case the workers' property rights can be fulfilled